PENGARUH HARGA, DISTRIBUSI DAN PROMOSI TERHADAP VOLUME PENJUALAN MOTOR HONDA BEAT - Wulandari, Nur; Suwarto, Suwarto; Fuadi, Selamet (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2021)
In an effort to increase sales volume, several efforts have been made by the company, namely determining a rational price level, providing a good distribution channel and conducting promotions to increase consumer buying interest. The purpose of this study was to determine the effect of price, distribution and promotion on the sales volume of Honda Beat motorcycles at PT. Tunas Dwipa Matra Tulang Bawang Barat.The method used in this research is explanatory survey method. This type of research is quantitative research with the research objects are price, distribution, promotion and sales volume. Population and sample in this study are reports on product prices, promotional costs and distribution costs at PT. Tunas Dwipa Matra, Tulang Bawang Barat Regency, 2019-2020. Documentation technique data collection. The analytical tool used is to use data quality analysis and multiple linear regression analysis with the SPSS program.The results showed that partially distribution and promotion had a positive and significant effect on sales volume, while price had no effect on sales volume. Simultaneously price, distribution and promotion simultaneously have a positive and significant effect on sales volume. Based on the coefficient number and the tcount value, it can be seen that the factor that most influences the sales volume is the distribution factor.